RESPON MAHASISWA TERHADAP PEMBELAJARAN MAHAROTUL QIRO’AH SECARA ONLINE PADA MASA PANDEMI COVID-19 - Siti Masruchah; Muhammad Afifullah; Kartika Ratnasari (FASHOHAH, 2021)
The Covid 19 pandemic that hits the world, including in Indonesia, had a significant impact on the education sector because it had to change in learning methods, as it was originally delivered offline and now at present, it needs to be delivered online.This article aims to describe the impact of the Covid-19 pandemic on reading skill learning (maharatul qira'ah), which currently also has to be carried out online. These changes certainly have an impact on the level of understanding of students, so thus, it is necessary to know to what extent the effectiveness of online learning is and whether the learning can be understood properly.The method used in this research is descriptive-qualitative. The data collected was generated from online observation and survey instruments. While the objects studied were students majoring in Arabic Language Education at Malang Islamic University and Maulana Malik Ibrahim State Islamic University of Malang.The results of this study indicate that learning reading skill which is carried out online actually encourages students to read Arabic texts more often, learn language rules, new vocabulary, also use media and learning applications so that the material being taught can be better received and not boring, also students are more enthusiastic in following the lessons. Key words: Learning reading skill (maharatul qira'ah), Arabic, Online, Covid-19